Psychopedagogy applied to the teaching-learning process in football tactics training: A bibliographic review - Pérez Murga, Cindy Polet; Laz Arechua, Judith Mariela; Estacio Alvear, Daniel Israel (Sport TK (Internet), 2024)
Research in sports psychopedagogy and its applied recommendations are characterized by a contrast between different learning theories in football tactics training. Traditional theories and their corresponding approaches for the specific case of teaching and learning how to play football are subject to compatibilities and incompatibilities. It is analyzed how behaviorism as an approach to teaching the game shows more incompatibilities with the nature of tactical actions compared to constructivism. As coaches strive to teach the game and get their players and team to perform, it is argued that teaching the game requires teaching approaches that will help develop their playing without taking away their autonomy and adaptability. The teaching-learning process during training to play soccer must be carried out to harmonize the characteristics of the content, the context and the individual in question. Finally, it is argued that coherent game design provides minimum conditions for teaching approaches, and that such design should be a priority when developing learning activities throughout the player development process. In conclusion, interactionist theory is the one that best serves for teaching the game and developing tactical behavior. Therefore, it is argued that its principles can help coaches adapt their own strategy for teaching the game to students. La investigación en psicopedagogía del deporte y sus recomendaciones aplicadas se caracterizan por un contraste entre las diferentes teorías de aprendizaje en el entrenamiento de tácticas en el fútbol. Las teorías tradicionales y sus correspondientes enfoques para el caso específico de enseñar y aprender cómo jugar al fútbol están sujetos a compatibilidades e incompatibilidades. Se analiza cómo el conductismo como un enfoque para enseñar el juego muestra más incompatibilidades con la naturaleza de las acciones tácticas en comparación con el constructivismo. A medida que los entrenadores se esfuerzan por enseñar el juego y hacer que sus jugadores y equipo rindan, se argumenta que enseñar el juego requiere enfoques de enseñanza que ayudarán a desarrollar su forma de jugar sin quitarles su autonomía y adaptabilidad. El proceso de enseñanza-aprendizaje durante el entrenamiento para jugar al futbol debe llevarse a cabo para armonizar las características de los contenidos, el contexto y el individuo en cuestión. Finalmente, se argumenta que el diseño coherente de los juegos proporciona condiciones mínimas para los enfoques de enseñanza, y que dicho diseño debe ser una prioridad al elaborar las actividades de aprendizaje a lo largo del proceso de desarrollo del jugador. Como conclusión, la teoría interaccionista es la que mejor sirve para la enseñanza del juego y el desarrollo del comportamiento táctico. Por lo tanto, se defiende que sus principios pueden ayudar a los entrenadores a adaptar su propia estrategia para enseñar el juego a los estudiantes.